Alleviation of lipopolysaccharide/d-galactosamine-induced liver injury in leukocyte cell-derived chemotaxin 2 deficient mice - Okumura, Akinori (Biochem Biophys Rep, 2017)
Leukocyte cell-derived chemotaxin 2 (LECT2) is a secreted pleiotropic protein that is mainly produced by the liver. We have previously shown that LECT2 plays an important role in the pathogenesis of inflammatory liver diseases. Lipopolysaccharide/d-galactosamine (LPS/d-GalN)-induced acute liver injury is a known animal model of fulminant hepatic failure. Here we found that this hepatic injury was alleviated in LECT2-deficient mice. The levels of TNF-α and IFN-γ, which mediate this hepatitis, had significantly decreased in these mice, with the decrease in IFN-γ production notably greater than that in TNF-α. We therefore analyzed IFN-γ-producing cells in liver mononuclear cells. Flow cytometric analysis showed significantly reduced IFN-γ production in hepatic NK and NKT cells in LECT2-deficient mice compared with in wild-type mice. We also demonstrated a decrease in IFN-γ production in LECT2-deficient mice after systemic administration of recombinant IL-12, which is known to induce IFN-γ in NK and NKT cells. These results indicate that a decrease of IFN-γ production in NK and NKT cells was involved in the alleviation of LPS/d-GalN-induced liver injury in LECT2-deficient mice.